Ramp Rate Influence on Synthesis of Sliced Porous Activated Carbon from Date Palm Tree by Physical Activation Method - Shoaib, Muhammad; M. Al-Swaidan, Hassan (Asian Journal of Chemistry, 2014)
Saudi Arabia is considered as a mass date producer all over the date producing countries around the world. Extensive amount of waste material is available in the form of date fronds because of the pruning process. Date fronds as a biomass is considered as a precursor for activated carbon production. The BET surface areas of the activated carbons prepared at a ramp rate of 5, 10, 20, 30 and 40 °C/min after 0.5 h activation time are 818, 1094, 1020, 565 and 784 m2/g, respectively. The activated carbon prepared at a ramp rate of 10 °C/min attains larger surface area 1094 m2/gm and can offer higher potential to produce activated carbon of greater adsorption capacity from bio mass such as date fronds. Supporting techniques like scanning electron microscopy verifies the pore generation too. Moreover by increasing the ramp rate from 10 and 20 °C/min the yield remains same i.e., 18.75 % whereas at a ramp rate of 40 °C/min the yield decreases from 20.3 to 16 %.